2014
DOI: 10.5694/mja14.00344
|View full text |Cite
|
Sign up to set email alerts
|

Survey of alcohol-related presentations to Australasian emergency departments

Abstract: Objective: To determine the proportion of alcohol‐related presentations to emergency departments (EDs) in Australia and New Zealand, at a single time point on a weekend night shift. Design, setting and participants: A point prevalence survey of ED patients either waiting to be seen or currently being seen conducted at 02:00 local time on 14 December 2013 in 106 EDs in Australia and New Zealand. Main outcome measures: The number of ED presentations that were alcohol‐related, defined using World Health Organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 197 publications
5
72
0
Order By: Relevance
“…It is known to underestimate the burden of alcohol on ED presentations 4, 6, 18. However, this does not exclude syndromic surveillance as a useful source of data for timely monitoring of acute alcohol harm trends at the state‐wide or local level.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is known to underestimate the burden of alcohol on ED presentations 4, 6, 18. However, this does not exclude syndromic surveillance as a useful source of data for timely monitoring of acute alcohol harm trends at the state‐wide or local level.…”
Section: Discussionmentioning
confidence: 99%
“…However, systematically identifying alcohol as a contributing factor to injury‐related ED presentations in NSW is not possible 4. As such, ‘late‐night’ arrival to the ED is commonly used as a surrogate measure of alcohol‐related injuries 21, 35, 38.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This survey found that one in seven presentations in Australia were alcoholrelated (14%); the rate for New Zealand was one in five (18%). 4 The second snapshot survey was conducted at 2.00 am on 6 December 2014. All EDs in Australia and New Zealand accredited by the Australasian College for Emergency Medicine (ACEM) for specialty training and non-accredited EDs that are part of the Emergency Medicine Education and Training (EMET) teaching network were invited to participate.…”
mentioning
confidence: 99%